REQUIREMENTS AND CONDITIONS OF CREATING A SECURITY SYSTEM BY THE ENTERPRISE AS A COMPONENT MANAGEMENT SYSTEM (Development Service Industry Management, 2024)
The security management system of an enterprise, institution, or institution is an integral, interconnected component of the overall management system. A detailed study of the state of security, when the management has an understanding of the real threats that may accompany or are already present, usually precedes and prompts the adoption of necessary measures for the formation of the enterprise's security management system. Timely response to existing and potential business threats, not according to the "residual principle", but preventively, is the most optimal strategy of enterprise management, which is able to ensure the presence of a separate service for its security.The conducted research also shows what legislative and legal basis managers and lawyers use in the process of training and formation of the company's security services, taking into account the specific features of its activity.The article examines the key aspects of the creation and functioning of an effective security system at the enterprise. the conceptual and terminological apparatus of enterprise security was elaborated, the principles of the formation and development of the enterprise security system, the components of this enterprise security system were defined and classified, and the content of the function of the enterprise security management system was described. Recommendations are offered for improving existing safety practices and implementing new technologies to ensure safety in the workplace.
Keywords: security system; enterprise; risk management; security policy; monitoring; business security; security technologies